2015
DOI: 10.1159/000431171
|View full text |Cite
|
Sign up to set email alerts
|

Dapsone Therapy for Pustular Psoriasis: Case Series and Review of the Literature

Abstract: Background: Pustular psoriasis is an uncommon psoriasis variant, clinically characterized as small sterile pustules on an erythematous base. Evidence for therapy is lacking, and many currently employed systemic therapeutics carry risks of significant side effects, without specifically targeting disease etiology which includes the aggregation of neutrophils. Observations: We report therapy with the anti-neutrophil agent dapsone in 5 patients with pustular psoriasis and provide a brief review of the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…A familial contribution is seen in some cases of pustular psoriasis, and one report suggested that there was a genetic component to SPD [16]. Both pustular psoriasis and SPD usually respond to dapsone [66][67][68][69].…”
Section: Differential Diagnosesmentioning
confidence: 99%
See 4 more Smart Citations
“…A familial contribution is seen in some cases of pustular psoriasis, and one report suggested that there was a genetic component to SPD [16]. Both pustular psoriasis and SPD usually respond to dapsone [66][67][68][69].…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…Maintenance therapy at a lower dosage is necessary to prevent relapse. Dapsone may cause hematologic adverse effects, such as methemoglobinemia, hemolytic anemia, agranulocytosis, hypersensitivity syndrome, renal toxicity, hepatic toxicity, or peripheral motor neuropathy [67,73]. Hemolytic reactions and agranulocytosis are dose dependent [67].…”
Section: Managementmentioning
confidence: 99%
See 3 more Smart Citations